Selection bias and competing risk. - Schooling, C Mary (American Journal of Epidemiology, 2025)
The article focuses on the advancements in understanding selection bias, particularly in the context of genetic studies and competing risks related to age at death. It highlights how selection bias can arise when individuals who have died before recruitment are excluded from studies, potentially leading to statistical errors and affecting causal inferences. The article also discusses the significance of disease-specific age at death patterns, illustrated with data from the United States in 2019, to better interpret studies involving long-term exposures and interventions. It emphasizes the need for precise information to mitigate biases and contextualize findings related to survival and disease outcomes.